KEABSAHAN PERKAWINAN POLIGAMI YANG IZINNYA DITETAPKAN PENGADILAN SETELAH PERKAWINAN (Studi Kasus Pengadilan Negeri Amlapura Nomor.77/Pdt.P/2022/PN.Amp.) - Reynaldi, I Wayan (Kerta Dyatmika, 2023)
Law Number 16 of 2019 concerning the Amendment to Law Number 1 of 1974 on Marriage is a general legal regulation that governs the fundamental aspects of marriage in Indonesia. Article 1 of the Law defines marriage as a physical and spiritual bond between a man and a woman as husband and wife. This research identifies a legal fact concerning the validity of a polygamous marriage in which the court-issued permission was granted after the marriage had already taken place. The purpose of this study is to examine the procedure for submitting an application for permission to have more than one wife under Law Number 16 of 2019, and to assess the validity of a polygamous marriage in cases where judicial permission was requested after the marriage occurred, as illustrated in Court Determination Number 77/Pdt.P/2022/PN.Amp. This study employs a normative legal research method, using a conceptual approach, a statutory approach, and a case-based approach. The results indicate that an application for polygamous marriage permission must be submitted to the District Court where the applicant resides, in accordance with prevailing legal provisions. The conclusion of the study is that a polygamous marriage conducted prior to obtaining a court’s approval may still be deemed legally valid, as shown in the Amlapura District Court Determination No. 77/Pdt.P/2022/PN.Amp dated October 21, 2022. Such marriage is considered lawful not merely to satisfy the sexual needs of the spouses but to fulfill the essential purpose of marriage namely, achieving the happiness and well-being of the husband, wife, and their children.